Comparative reservoir limnology in Juramento (Salta) and Salí-Dulce (Tucumán) Basins in Argentina - Salusso, María Mónica; Moraña, Liliana Beatriz (Revista de Biología Tropical, 2018)
The reservoirs of the upper Juramento basin (Cabra Corral and El Tunal) and the Salí-Dulce basin (El Cadillal, Río Hondo, and Escaba) show certain peculiarities due to their geographical location, basin morphology and limnological features. Such peculiarities were compared during significant algal bloom periods between 2002 and 2008, by analyzing the main physicochemical parameters and ecological attributes of the phytoplankton assemblages using standard methods. Tucumán reservoirs were different in most variables showing higher values of conductivity, nutrients and algal biomass. Regarding the hydrological cycle, El Cadillal exhibited the lowest biomass average (2.74 mg Chl.m-3) during maximum water flows, whereas the Cabra Corral lacustrine zone exhibited the highest biomass average (63.36 mg Chl.m-3) during minimum water flows. For the same period, the Cabra Corral lacustrine zone exhibited lower phytoplankton diversity and richness (1.37 and 9, respectively), in accordance with dinophyte blooms of Ceratium sp. In all reservoirs, the following biological variables showed a significant contrast in the hydrological cycle: highest phytoplankton biomass during minimum water flows (35.68 mg Chl-a m-3) vs. waterfloods (13.68 mg Chl-a m-3) (T = 3.42, P = 0.001). During minimum water flows, richness (14.30 sp.) and equitability (0.51) were lower vs. waterfloods (20.23, 0.59, respectively) (T = 2.36; P = 0.0196), as a result of the allochthonous nutrients provided by the main tributaries. Management of the reservoirs’ hydrometric levels during dry season determines the deterioration of the water quality with increased algal blooms. In order to ensure the systems’ sustainability, eutrophication must be controlled with programs to reduce diffuse nutrient loads and to treat residential and agroindustrial effluents, particularly in Sali-Dulce basin.